Towards the Evaluation of the Ecological Effectiveness of the Principles, Criteria and Indicators (PCI) of the Forest Stewardship Council (FSC): case study in the Arkhangelsk Region in the Russian Federation - Blumroeder, Jeanette Silvin; Hobson, Peter Ralph; Graebener, Uli Frank; Krüger, Joerg-Andreas; Dobrynin, Denis; Burova, Natalya; Amosa, Irina; Winter, Susanne; Ibisch, Pierre Leonhard (Challenges in Sustainability, 2018)
The Forest Stewardship Council (FSC) is a voluntary sustainability standard with global reach that has been developed to encourage responsible and sustainable forest management. Despite its broad appeal, there is little scientific assessment to substantiate the effectiveness of FSC in the boreal zone. In this study, an ecosystem-based and participatory approach was applied to a case study in the Arkhangelsk Region of the Russia Federation to assess the potential influence of the principles, criteria and indicators of the Russian FSC standard. An ECOSEFFECT theoretical plausibility analysis was conducted to evaluate the potential effectiveness of FSC in safeguarding the ecological integrity of the ecosystem. Besides spatial analysis and a field visitation, core elements of the methodological procedure were workshops with experts and stakeholders who directly contributed to knowledge mapping and analysis. The results of the study suggest FSC can potentially influence and improve forest management including monitoring and evaluation, foster the institutional capacity, and enhance knowledge on the impacts of forest management. Theoretically, FSC has a certain potential to reduce a range of anthropogenic threats to the ecosystem, such as large-scale deforestation and forest degradation, logging of High Conservation Value Forests, large size of clear-cuts, excessive annual allowable cuts, damage to trees during forest operations, and hydrological changes. However, human-induced fire is the only ecological stress that was assumed to be effectively tackled through a strong and positive influence of FSC. The results of the theoretical analysis with a semi-quantitative evaluation revealed the potential for FSC to generate much more effective outcomes for biodiversity by prudently targeting key ecological problems. The biggest problem is the large-scale clear-cutting practice, especially within IFL. These devastating practices are not promoted by, but are compliant with the current Russian FSC standard. This feeds doubts ...